Kajian Yuridis mengenai Rahasia Bank untuk Kepentingan Perpajakan - Irma Suryani; Mohammad Ghufron AZ; Dewi Astutty Mochtar (University of Merdeka Malang, 2021)
Legality for tax officers to know customer data, without having to get approval from Bank Indonesia, enough through the approval of the Minister of Finance is regulated by Law Number 9 of 2017 concerning Access to financial information for tax purposes. This research examines how the regulation regarding customer data information at financial institutions after the issuance of Law Number 9 of 2017 concerning Access to Financial Information for Taxation Purposes and how is legal certainty regarding bank secrecy after the issuance of Law Number 9 of 2017 concerning Access to Financial Information for Purposes Taxation. This study uses a normative juridical approach. This approach focuses on examining laws and regulations concerning confidential customer data information as well as book material in the form of books and other legal journals related to these issues. The result of this research is that after the issuance of Law Number 9 of 2017 concerning Access to Financial Information for tax purposes, the taxation authorities have full authority and authority in accessing each customer’s data from banks and the principle of bank secrecy related to customer data protectionafter the issuance of Law Number 9 of 2017 concerning Access to Financial Information for Taxation Purposes is still ongoing and applies as long as it is outside of what is stipulated in the law.